Back Cover: Rapid and Quantitative Assessment of Redox Conduction Across Electroactive Biofilms by using Double Potential Step Chronoamperometry (ChemElectroChem 5/2017). Issue 5 (28th April 2017) - Zhang, Xu; Philips, Jo; Roume, Hugo; Guo, Kun; Rabaey, Korneel; Prévoteau, Antonin
Abstract : The Back Cover picture illustrates the discharge of an electroactive biofilm recorded by double potential step chronoamperometry, allowing the fast determination of charge‐transfer parameters across the biofilm (Artwork: A. Landi). More information can be found in the Article by A. Prévoteau and co‐workers onpage 1026 in Issue 5, 2017 (DOI:10.1002/celc.201600853 ).